(untitled) (Bangladesh Journal of Physics, 2023)
The rising expectations for the introduction of nuclear power to solve dire energy shortages and to meet the future increased demand are the priorities for Bangladesh. Nuclear power is a future source of energy; therefore, Bangladesh needs to establish the necessary infrastructure to build a twin unit plant at the Rooppur site, aiming to achieve generation of 2400 MW (e) by the year 2024-2025 respectively. For the realization of a safe and secured project site for the construction of a nuclear power plant, necessary site-specific investigations for the description of geography and demography, geodynamic and seismic conditions, hydrological and morphological characteristics, geological and hydro-geological conditions, meteorological and aerologic situations, man-caused conditions are essential. Procedures are presented for investigating the seismic hazard within the Rooppur Nuclear Power Plant (NPP) construction area. This study reveals the relation between seismic acceleration and potential damage. Such design basis parameters are determined based on the correlation between seismic acceleration versus potential damages due to earthquakes. The geotechnical parameters for the nuclear power project site in Bangladesh have been estimated. The estimated data of the peak ground acceleration and other geophysical parameters described the suitability for the Rooppur NPP. The design basis earthquake safety-related parameters are determined which helps us in determining a suitable nuclear power technology appropriate for Bangladesh. Bangladesh Journal of Physics, Vol. 30, Issue 2, pp. 69–76, December 2023